Scaling up participatory plant breeding sustainable seed delivery systems for meeting farmers' needs for diversity and varietal change over time - Rattunde, E (International Crops Research Institute for the Semi-Arid Tropics, 2002)
Detailed analyses of seeds available at household level were carried out in two villages.